2020
DOI: 10.1021/acs.orglett.0c01011
|View full text |Cite
|
Sign up to set email alerts
|

Palladium-Catalyzed Tandem Dehydrogenative [4 + 2] Annulation of Terminal Olefins with N-Sulfonyl Amides via C–H Activations

Abstract: A palladium-catalyzed tandem dehydrogenative [4 + 2] annulation of terminal olefins with N-sulfonyl amides via C(sp 2 )−H activation, allylic C(sp 3 )−H activation, and homoallylic C(sp 3 )−H elimination processes has been developed. Promoted by the DMSO ligand, various benzamides, heterocyclic arylamides, alkenyl carboxamides, and commercial olefins are found to be efficient substrates to construct important heterocyclic compounds bearing a vinyl substituent with high E stereoselectivity. Using air as the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 82 publications
0
5
0
Order By: Relevance
“…Under the optimal conditions, the scope and limitations of this method in synthesizing pyrroles 3 were investigated. 19 On one hand, when enaminone 1a was fixed to react with different acrylic ester substrates, the products containing a methyl, ethyl, n-butyl, tert-butyl, or benzyl group (3a−3e and 3q−3u, Scheme 1) were afforded in good yields. The extension of the alkene component to internal alkenyl ester, enone, vinyl nitrile, vinyl amide, styrene, and α-allylnaphthalene was also conducted, but none gave the expected pyrrole product under the present conditions (see also Scheme S2 in the Supporting Information).…”
mentioning
confidence: 99%
“…Under the optimal conditions, the scope and limitations of this method in synthesizing pyrroles 3 were investigated. 19 On one hand, when enaminone 1a was fixed to react with different acrylic ester substrates, the products containing a methyl, ethyl, n-butyl, tert-butyl, or benzyl group (3a−3e and 3q−3u, Scheme 1) were afforded in good yields. The extension of the alkene component to internal alkenyl ester, enone, vinyl nitrile, vinyl amide, styrene, and α-allylnaphthalene was also conducted, but none gave the expected pyrrole product under the present conditions (see also Scheme S2 in the Supporting Information).…”
mentioning
confidence: 99%
“…In 2020, Wang and co-workers developed a tandem dehydrogenative [4 + 2] annulation reaction of terminal olefins with N-sulfonyl amides 116 via Pd-catalyzed C(sp 2 )À H allylation/aminopalladation/β-H elimination processes to produce 3,4-dihydroisoquinolones 119 (Scheme 30a). [73] With the assistance of the DMSO ligand and the CONHNs directing group, a fivemembered palladacycle 118 a can be formed smoothly, which further coordinates with olefin and removal of an allylic hydrogen giving the π-allyl palladium using allylbenzenes as alternative substrates, it was possible to obtain isoquinolinone products 120 within a similar Pd(TFA) 2 /Cu(OAc) 2 catalytic system (Scheme 30b). [74]…”
Section: Annulationmentioning
confidence: 99%
“…In 2020, Wang et al explored a palladium-catalyzed tandem dehydrogenative [4 + 2] annulation approach for the synthesis of complex heterocyclic compounds from terminal olefins 44 with N -sulfonyl amides 43 (Scheme 23). 35 This protocol featured a broad substrate scope and the use of environmentally friendly air as the oxidant. Screening of various ligands showed that the use of DMSO significantly improved the reaction yield, probably because the in situ formed Pd(DMSO) 2 (TFA) 2 catalyst exhibits both hard O- and soft S-bound DMSO ligands, which can take part in the interconversion between the relatively hard Pd( ii ) and soft Pd(0) redox states.…”
Section: Palladium-catalyzed C–h Annulationmentioning
confidence: 99%